The effect of Cobalt alloy nanocrystalline coating on tensile properties and surface performance of mild steel / Mohd Zakuan Zabri, Nik Rozlin Nik Masdek and Koay Mei Hyie - Zabri, Mohd Zakuan; Nik Masdek, Nik Rozlin; Koay, Mei Hyie (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Coatings are frequently used to enhance the mechanical and physical characteristics of mild steel by protecting mild steel surfaces against corrosion. Corrosion might attack surface without proper coating method which may lead to structural failures and increase maintenance cost. The main objective of this study is to investigate the effect of CoNiFe nanocrystalline coating on surface roughness, hardness, and tensile performance of mild steel substrate. Different parameters were introduced, such as current, pH, deposition times and heat treatment to analyse surface roughness, hardness, and tensile strength of CoNiFe nanocrystalline coating. The lowest surface roughness of 2.14 μm was recorded by CoNiFe nanocrystalline coating with 30 minutes deposition time at pH 3, I: 3 A and heat treated, while the highest recorded surface roughness of 4.233 μm was detected on uncoated mild steel. The highest improvement of microhardness was observed on CoNiFe nanocrystalline coating with 45 minutes deposition time at pH 3, I: 1.5 A and heat treated (393.6 Hv) as compared to the uncoated mild steel (171.44 Hv). Tensile performance of CoNiFe nanocrystalline coating with 45 minutes deposition time at pH 3, I: 1.5 A and heat treated was the highest with yield stress and ultimate tensile stress of 472.35 MPa and 559.11 MPa, respectively. The lowest tensile performance was recorded by uncoated mild steel with yield stress and ultimate tensile stress of 149.40 MPa and 186.78 MPa, respectively.